Trastorno de ansiedad por separación en la infancia y la adaptación escolar de una niña de 3 años - Sánchez Bajaña, Rosa Lisseth (2019)
The current case study is aimed at a 3-year-old girl who entered the Carlos Luis Morales Reina Comprehensive Care Center in the Babahoyo canton of the province of Los Ríos, in which cognitive behavioral therapy was applied, which was In the process of adapting to the school stage for which her mother asked for psychological help, for the development of this clinical case, 4 sessions were carried out in which the techniques were applied to reduce anxiety in the girl and eradicate the irrational thoughts she has . This is an exclusive case for which a 3-year-old girl finds it difficult to adapt to the school environment, in which she aims to apply the cognitive behavioral technique to reduce the anxiety caused by separation and school adaptation anxiety disorder, it is This is why cognitive behavioral therapy was applied with cognitive restructuring, relaxation and playful techniques so that the anxiety that it gives you when you separate from your parent can be reduced, to obtain the results of these techniques, the scale of Spence's childhood anxiety before and after so that it can be done by means of a tool to verify that the girl as she responded to the therapy, where it could be concluded that with the application of these techniques the girl could adapt favorably to her new environment that is the school